Genetic variation of the nuclear sequences of mitochondrial origin associated with retrotransposon Tv1 insertions in Drosophila species of the virilis group - B. V. Andrianov; D. A. Romanov; T. V. Gorelova (Вавиловский журнал генетики и селекции)
Mitochondrial DNA sequences integrated into chromosomes are a promising object for designing genetic markers for studies of phylogenesis and genomic instability. Mitochondrial genomes of D. virilis and other Drosophila species of the virilis group contain (AT)n microsatellites in the spacer region between the atp6 and cox3 genes, and this microsatellite sequence is one of the hallmarks of the virilis group. The nuclear genome of D. virilis contains many extended fragments of mitochondrial DNA, which in total are several times longer than the mitochondrial genome. These nuclear sequences of mitochondrial origin contain all types of mitochondrial sequences, including mitochondrial genes and the aforementioned microsatellite sequence. The presence of the (AT)n microsatellite allows insertion of retrotransposon Tv1, which can transpose into the (AT)n microsatellite in a site-specific manner. The Tv1 insertion into (AT)n, close to the atp6 or cox3 pseudogenes produces a unique sequence. This sequence is formed by retrotransposon Tv1 and pseudogenes atp6 or cox3. This unique sequence can be detected in the genome by a PCR-based method. We applied this method to the detection and analysis of the nucleotide variability of the pseudogenes atp6 and cox3 associated with Tv1 insertions in a D. virilis cell culture and in the genomes of four Drosophila species of the virilis group: D. virilis, D. montana, D. borealis, and D. lacicola. We discovered new events of mitochondrial sequence transfer to the nucleus in the transplanted cell culture of D. virilis, and new Tv1 insertions, having emerged during the passage of this cell line were detected in the genome of the D. virilis transplanted cell culture. We found atp6 and cox3 pseudogenes associated with insertions of retrotransposon Tv1 in the nuclear genomes of four Drosophila species from the virilis group. These chimeric sequences proved to be species-specific. The age of the Tv1 insertion into the atp6 and cox3 pseudogenes is estimated at 1.50 Ma for D. virilis, 1.31 Ma for D. lacicola, and 1.56 Ma for D. borealis. A specific situation was revealed for D. montana, in which Tv1 insertions with nearly identical 5' and 3' long terminal repeats (LTRs) were present in accessions of flies from Europe and Asia. The age of this insertion was about 300 thousand years, and the insertion was absent from the D. montana fly line from North America.